2022
DOI: 10.1111/beer.12497
|View full text |Cite
|
Sign up to set email alerts
|

A fear‐based view of wisdom: The role of leader fear of failure and psychological empowerment

Abstract: Leader wisdom is crucial to effective organizations because it is one of the greatest human capacities. However, understanding what factors impact leader wisdom is still developing. In this paper, we rely on a fear-based view of wisdom and empirically examine through a quantitative study of 249 leaders if one of the primary regulators of human behavior (fear) is positively related to wisdom. We are specifically focused on the role of fear of failure and wisdom. Additionally, because we recognize that fear has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…Indeed, only a few studies assessed leader fear in organizations, yielding mixed findings. While some studies provided evidence for the negative effects of leader fearful states (Mohan, Voss, & Jiménez, 2017;Wisse, Rus, Keller, & Sleebos, 2019), other studies reported non-significant (Eisenberger et al, 2014;Lagios, Restubog, Garcia, & Caesens, 2023) or even positive (Solansky, Wang, & Quansah, 2023) effects. As environmental disruptions such as pandemics are tough managerial concerns (Kim, Vaiman, & Sanders, 2022), advancing our understanding of the specific relationship between leaders' fear of COVID-19 and employee performance may help derive management strategies to enable leaders to turn their negative emotional states into drivers of effective leadership and improve employee proficiency.…”
Section: Promotes Employee Performancementioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, only a few studies assessed leader fear in organizations, yielding mixed findings. While some studies provided evidence for the negative effects of leader fearful states (Mohan, Voss, & Jiménez, 2017;Wisse, Rus, Keller, & Sleebos, 2019), other studies reported non-significant (Eisenberger et al, 2014;Lagios, Restubog, Garcia, & Caesens, 2023) or even positive (Solansky, Wang, & Quansah, 2023) effects. As environmental disruptions such as pandemics are tough managerial concerns (Kim, Vaiman, & Sanders, 2022), advancing our understanding of the specific relationship between leaders' fear of COVID-19 and employee performance may help derive management strategies to enable leaders to turn their negative emotional states into drivers of effective leadership and improve employee proficiency.…”
Section: Promotes Employee Performancementioning
confidence: 99%
“…Eisenberger et al (2014) reported supervisor fear of exploitation in interpersonal relationships to be unrelated to subordinates' perceptions of leader-member exchange, and Lagios et al (2023) found supervisor fear or retaliation to be unrelated to supervisor undermining behavior. Finally, Solansky et al (2023) provided evidence for the benefits of leader fear of failure for leader psychological empowerment and wisdom.…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…On the other hand, they usually show various inward and outward attacking forms, such as self-injury, suicide, impulsion, agitation, and so on. Depression is likely to be a predictive factor of NSSI behaviors because not only can it hurt their bodies and threaten their lives, but may also bring threats to others ( 16 ). Depression symptoms are closely related to aggressive behaviors and boys with depression have more serious and diversified criminal behaviors ( 17 ).…”
Section: Introductionmentioning
confidence: 99%